Mechatronic systems and process automation : model-driven approach and practical design guidelines - Kaltjob, Patrick O. J. (Boca Raton, FL : Taylor & Francis, CRC Press, 2018)
The book discusses the concept of process automation and mechatronic system design, while offering a unified approach and methodology for the modeling, analysis, automation and control, networking, monitoring, and sensing of various machines and processes from single electrical-driven machines to large-scale industrial process operations. This step-by-step guide covers design applications from various engineering disciplines (mechanical, chemical, electrical, computer, biomedical) through real-life mechatronics problems and industrial automation case studies with topics such as manufacturing, power grid, cement production, wind generator, oil refining, incubator, etc."--Provided by publisher.
Electrical-driven actuating elements : modeling and selection -- Logic controller design -- Process monitoring, fault detection, and diagnosis -- Sensing and data acquisition elements : modeling and selection -- Data transmission system.
Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc.
Includes bibliographical references and index.
EEE
Keywords: Mechatronics; Manufacturing processes -- Automation; Electrical engineering